Income Trajectories and Subjective Well-Being: Linking Administrative Records and Survey Data - Schöllgen, Ina; Kersten, Norbert; Rose, Uwe (International journal of environmental research and public health, 2019)
An association between income and life satisfaction has been well documented, however, little is known of how income trajectories affect different facets of subjective well-being (SWB). The aim of this study was to examine how several aspects of income dynamics are related to life satisfaction and affect balance. Longitudinal information on income from administrative records covering 13 years (1999–2011) is linked to cross-sectional data on SWB collected in 2011/12 from the nationally representative Study on Mental Health at Work (S-MGA; n = 3364). Parameters from subject-specific regression analyses of income over time were used as indicators of income development in regressions over all participants, conducted separately for men and women. Associations between income and life satisfaction were stronger and more consistent than associations between income and affect balance. Major findings were that longer-term income change was more strongly related to SWB than current deviation from expected income. Higher stability in income development was associated with higher SWB. A higher share of income from benefits predicted lower life satisfaction and a more negative affect balance. Our results show the importance of examining income trajectories and taking into account source of income to gain a more differentiated view on the income-SWB association.